Study of Flow between Non-Isothermal Disks in Hydro-Viscous Drive - Jianzhong Cui (Japanese Society of Tribologists, 2018)
The film flow between the disks is the critical factor in the design of hydro-viscous drive. In the previous work dealing with the flow in the gap, few authors considered the effect of non-isothermal interface on the flow. In order to investigate the dynamic behavior of the oil film between non-isothermal friction pair in hydro-viscous drive, the flow field of the oil film between the disks is presented with consideration of four representative temperature models. Parameters related to the flow, such as temperature, pressure, velocity, shear stress and viscous torque are obtained by means of numerical simulation. The results show that non-isothermal interface results in temperature distribution profiles that diverge from the ideal parabolic curve. Both the discrepancies about film pressure and radial velocity at the outlet are vulnerable to temperature variation derived from a set of frictional pair. Tangential velocity profiles diverge from inlet to outlet due to the non-isothermal interface. Shear stress profiles show the opposite trend caused by the substantial variation about the oil viscosity. The research results lay a theoretical foundation for the reasonable designs of hydro-viscous drive.